Ações de saúde mental por agentes comunitários de saúde: investigando uma experiência de saúde mental na atenção básica - Marcelo Arinos Drummond Junior (2009)
The purpose of the actual piece of work is the investigation of a Mental Health care experience in Primary Care, performed by Community Health Workers (CHW) working at a basic health unit in the district of Betim, Minas Gerais State. The inclusion of Mental Heath practices in Family Health is part of Brazilian public policies. The Family Health teams are integrated by the Community Health Workers, sanitary workers who necessarily inhabit the community where their action is to take place, and whose activities were defined by the Community Health Workers´ Program. There are no national policies for Mental Health care specifically directed to these professionals. The qualitative methodology was used in this research. Primary data were obtained by six semistructured interviews done with the Community Health Workers in question, by means of two semistructured interviews done with university degree technicians, who also participated of this experience giving support to the CHW`s actions. This data was also collected during three participant observation visits in a therapeutic workshop coordinated by the CHW. The Thematic Content Analysis guided the analysis of the obtained data. The theoretical references used in this process are the recommendations for the organization of the Primary Care in health expressed by the Alma Ata Declaration and the principles and experiences of deinstitutionalization based on basaglian tradition. The collected material was distributed in three main themes: Locally Originated Happenings, Mental Health Care by the Community Health Workers, and Meanings of a Practice. One concludes that the experience was conceived during the meetings organized by the units psychologist aiming the reduction of conflicts inside the CHW teams. Theses Professional begun to ask questions, during these meetings, concerning the mental suffering cases from their territory of action and to put in question the difficulty of ambulatorial treatment access of these cases, that happend at the Health Unit. As an immediate consequence, a mechanism named The Reception Room was instituted, in order to welcome the demanding cases. The meetings at The Reception Room always took place in the presence of the CHW. This initiative is supposed to have allowed them to practice their listening. The action of the CHW in Mental Health was based on the knowledge they acquired in an educational process that occurred at weekly team meetings in which both the CHW and the university degree technicians discussed the cases. It is possible to see that not only did the CHW identify the new cases, follow the ones in treatment in order to systematically observe their mental state, set them out to university degree technicians (actions that were always planed and discussed at the teams meetings), but also carried out the following of the cases for which they were responsible, using the mechanism of listening and the affective dimension of the therapeutic relationship. The broadening of horizons, the capacity of accepting the individual differences and capacity of listening to the other, the comprehension of the importance of their role in the healing of the users of the health system and affective bond established with them are an important part of the universe of meanings the CHW attribute to their practice.